AN ANALYSIS OF TABOO LANGUAGE IN THE ANIMATED DIALOGUE OF TEKOTOK EPISODE: NUMPANG KOSAN, NASIBNYA SENTOT, A STORY OF A FIRST CHILD - Wahyu Hidayat; Prissilia Prahesta Waningyun; Rissa Filyang (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study is motivated by the widespread use of taboo language in digital communication, particularly in animated media. It aims to describe the forms of taboo language, analyze their functions, and examine their contextual meanings and the underlying social factors in the dialogues of the Tekotok animation, specifically in the episodes Numpang Kosan, Nasibnya Sentot, and Cerita Anak Pertama. This research employs a sociolinguistic approach using a descriptive qualitative method. The data were collected from the dialogues in Tekotok animated videos through observation and note-taking techniques, and then analyzed through the stages of reduction, classification, and interpretation. The findings reveal that taboo language in Tekotok animation appears in various forms, such as swearing, insults, vulgar terms, and figurative expressions. Taboo language is no longer used merely in its lexical sense, but functions as a means of expressing emotions, satire, insults, and social criticism. In addition, a shift in meaning is identified, where words that were not originally considered taboo can become taboo due to word combinations and the context of their use. This indicates that taboo language is dynamic, contextual, and serves communicative functions in shaping characters and conveying social messages in digital media.